PENERAPAN METODE EKSPERIMEN UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN IPAS MATERI PERUBAHAN ENERGI KELAS IV: APPLICATION OF EXPERIMENTAL METHODS TO IMPROVE STUDENTS' LEARNING OUTCOMES IN THE SUBJECT OF SCIENCE ON ENERGY CHANGES CLASS IV - Firdausi, Rofiqoh; Khoridattul Huda, Moh. (Jurnal Al-Ilmu: Jurnal Penelitian dan Pendidikan Madrasah Ibtidaiyah, 2025)
This learning outcome, namely the lack of application of learning methods so that it hinders the learning process which causes the low learning outcomes of IPAS students in class IV MI Bustanul Ulum Wadung Pakisaji. Other factors in the learning process that affect learning activities and outcomes such as: 1) the way teachers learn in class still uses conventional methods, 2) lack of adequate learning media for teachers to use in class, making it difficult for students to understand concepts so that student learning outcomes are low, 3) no application or experimentation of experimental methods, 4) less active in learning this can be seen from the intensity of students asking questions and providing answers or responses. Based on the findings of the researchers, the solution offered is the application of the experimental method of energy change material.The formulation of the problem in this study is: Can the application of experimental methods improve student learning outcomes in the subject of IPAS material on energy changes in class IV MI? The purpose of the study was to determine whether the use of experimental methods can improve the learning outcomes of fourth grade students in the subject of IPAS energy change material.The research used is Classroom Action Research (PTK) with a quantitative approach. The PTK model used is the Kemmis and Mc Taggart model. Researchers conducted research through two cycles, namely Cycle I two meetings and Cycle II two meetings. In the subject of IPAS material on energy changes in class IV MI. The steps are as follows: 1) Planning, 2) Implementation, 3) Observation, 4) Reflection. In collecting data, researchers used written test sheet instruments, observation sheets, and interview guidelines. Data analysis shows that classroom action research carried out in two cycles, the application of experimental methods in learning IPAS material on energy changes can improve the learning outcomes of fourth grade students of Madrasah Ibtidaiyah Bustanul Ulum Pakisaji. It can be seen in the value of Cycle I with the percentage of learner activity reaching 50% and the percentage of completeness reaching 66% with an average score of 67.5. In Cycle II, there was a significant increase with a percentage of learning activities of 88% and a percentage of completeness of 83% with a successful category with an average value of 84.66. Therefore, the experimental method can be said to be feasible and effective to use in learning.